Li-8 in GaAs studied with beta-NMR - Dunlop, T; Mansour, A; Salman, Z; Chow, K; Fan, I; Jung, J; Kiefl, R; Kreitman, SR; Levy, C; MacFarlane, W; Morris, G; Parolin, T (2007)
beta-NMR has been used to study isolated spin polarized Li-8(+) in bulk crystalline GaAs. At low temperatures a large fraction (at least 70%) of the Li end up in locations with cubic symmetry (e.g. a tetrahedral interstitial site). The linewidth of the beta-NMR Li-8(+) resonance increases dramatically above 150K, and reaches a maximum at about 290K. These results are consistent with a site change from an interstitial to a substitutional beginning at approximate to 150 K. The field dependence of the linewidth at 100 K is also discussed. (C) 2007 Elsevier B.V. All rights reserved.